The role of policy in supporting SSS – the case of Quebec. Issue 2 (17th February 2022) - Talbot, David; Boiral, Olivier
ABSTRACT: Since the early 2000s, short sea shipping (SSS) is often associated with significant social and environmental benefits. To encourage a modal shift, several nations around the world have developed public SSS policies. However, the policies' effectiveness are increasingly being questioned in the public arena. Therefore, the current article's primary objective is to assess one of these SSS public initiatives' legitimacy. In particular, we analyzed Quebec's PREGTI initiative, which is designed to both reduce greenhouse gas (GHG) emissions and promote local SSS development. Our findings are based on a triangulated analysis of official PREGTI documents and semi-structured interviews with local marine-sector specialists (N = 36). The data analyses inspired the development of an integrative framework that includes four components that could explain the lack of SSS program credibility and interest. Our framework identified critical issues for consideration in SSS program development, including: 1) the institutional framework's relevance; 2) its implementation challenges; 3) the program's predictability; and 4) the credibility of government authorities. Ultimately, the present article provides a better understanding of the significant discrepancies between public SSS programs development and the needs of local maritime sector stakeholders.